Isolation and molecular characterization of multidrug-resistant Salmonella enterica serovars - Mysoon M. Al-Ansari; Moneerah M. Aljubali; Ali M. Somily; Ahmad M. Albarrag; Afshan Masood (Elsevier, 2021)
Background: Salmonellosis is a foodborne zoonosis leaving gastrointestinal illness and drug-resistant genes to the consumers. To prevent Salmonella contamination associated health issues in the chicken meat sold in Riyadh city in Saudi Arabia. The evaluation of the Salmonella isolates from the meat sample needs to be screened for the composition of Salmonella serotypes and antimicrobial resistance pattern at the molecular level. Methods and results: Using specific growth media for Salmonella spp., swabs taken from the whole-body surfaces of 200 chilled broiler chickens from different vendors in the city of Riyadh, were screened for Salmonella contamination. Biochemical and molecular characterization of the isolates showed the presence of the serovars, Salmonella enterica, Salmonella Enteritidis, S. Typhimurium, S. Kentucky, and S. Tennessee. The isolated serovars exhibited multidrug resistance [MDR] resistance to antibiotics. Molecular characterization of the different serovars shows the presence of sixteen drug-resistant genes. The drug resistance mechanism at the molecular level varied with serotypes according to the nature of the antibiotics they encountered. A comparative study of the nature of the drug-resistant gene and the common antibiotics used in poultry farming in that province matches much, indicating adaptive variation in S. enterica serotypes to survive in the host's gut biome. The resistance genes from the chicken meat have every chance to get into the human system. The native microbes in consumers may acquire drug-resistant genes from S. entericus serovars. Such conditions may lead to treatment complications in the hosts. Conclusions: The results indicated that Salmonella infections constituted a potential risk to consumers through chicken flocks and noted that the genotypic resistance pattern to antibiotics draws attention in terms of both human and animal health. Also, promote other options for poultry farming, avoiding antibiotics supplementation.